Hidrodynamics influence assessment on Mondego Estuary eutrophication process - Duarte, António A. L. Sampaio (2002)
The south arm of Mondego estuary is stressing by an eutrophication process due to massive nutrient loading from urbanised areas and diffusive runoff from intensively agricultural areas. A sampling program was carried out at three benthic sample points and at three other sites (river Pranto sluice, Armazéns channel mouth and Gala bridge) for water column monitoring. Available field data analysis allows concluding that the occurrence of green macroalgal blooms is strongly dependent on the hydrodynamic conditions, precipitation and salinity gradients. The aim of this work is to assess the role of estuarine hydrodynamics on the non-attached macroalgae control and the magnitude of nutrients tidal balance. Residence times estimation, allowed by mathematical modelling, can provide essential information about estuarine hydrodynamic behaviour, considering different scenarios, in order to select the better water quality management practises.